2009
DOI: 10.1088/0957-4484/20/12/125601
|View full text |Cite
|
Sign up to set email alerts
|

Ordered CdS micro/nanostructures on CdSe nanostructures

Abstract: Composite structures of aligned and orientation-ordered quasi-one-dimensional CdS micro/nanostructures on CdSe substrates of different shaped nanostructures have been synthesized by using two-step thermal evaporation processes. The CdSe substrate crystalline orientations and local temperatures play their roles in the CdS nanostructure growth step, which is in some contrast with the vapor-liquid-solid (VLS) growth mechanism. Micro-photoluminescence measurements show strong luminescence responses on the six-fold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Si/CdSe heterostructures were obtained by one-step metal-catalyzed thermal evaporation method and their time-resolved X-ray-excited optical luminescence was characterized [108,109]. Dai et al showed the growth of hierarchical CdSe/CdS nanostructures by a two-step thermal evaporation method [110]. However, doping in CdSe nanostructures remains problematic and very few reports concerned about this issue, while the doped CdSe nanostructures do show interesting properties.…”
Section: Cdsementioning
confidence: 99%
“…Si/CdSe heterostructures were obtained by one-step metal-catalyzed thermal evaporation method and their time-resolved X-ray-excited optical luminescence was characterized [108,109]. Dai et al showed the growth of hierarchical CdSe/CdS nanostructures by a two-step thermal evaporation method [110]. However, doping in CdSe nanostructures remains problematic and very few reports concerned about this issue, while the doped CdSe nanostructures do show interesting properties.…”
Section: Cdsementioning
confidence: 99%
“…Most hetero (or composite) structures are prepared in two steps. As examples, 1D ZnS/CdS heterostructures or ordered CdS micro/nanostructures on CdSe nanostructures were fabricated via a two-step thermal evaporation method; hierarchical assembly of ZnO nanostructures on SnO 2 backbone nanowires or branched ZnS/ZnO heterostructure were prepared by a thermal evaporation process followed by hydrothermal growth; one-dimensional CdS/ZnO core/shell nanofibers were made by spinneret electrospinning. So far, there are very few report on the fabrication of CdO nanowires, especially none on the branched CdO/ZnO core/shell heterojunction nanowires, by simple chemical vapour deposition (CVD) methods. , …”
Section: Introductionmentioning
confidence: 99%
“…Masaru Kuno's group reported the successful fabrication of CdSe/CdS core/shell NW by using a solution-phase chemistry method [13], but the shell layer is polycrystalline and randomly attached on the core surface. In past decade, considerable progresses have been achieved in fabricating crystalline NWs heterostructures by optimizing chemical vapor deposition (CVD) method [14][15][16][17]. However, to best of knowledge, controllable assemble of crystalline CdSe/CdS core/shell NW has not been achieved so far.…”
Section: Introductionmentioning
confidence: 99%